22q11.2 Deletion Syndrome and Dosage Effects of Candidate Genes a Review and Promoter Analysis of PRODH Gene - Kiran Kumar HB; Tanuja Prakash; Rama Thyloor; Manjunatha B.K; Pallavi devaraja; Mukunda Suryanarayana (Research Perspective on Biological Science Vol. 1, 2025)
22q11.2 deletion syndrome (22q11.2DS), also known as Velo-Cardio-Facial Syndrome (VCFS) or DiGeorge Syndrome, is a genetic disorder due to a microdeletion on chromosome 22-q11.2. The clinical phenotype, which is complex and variable, includes specific congenital defects of the cardiovascular system, craniofacial and immune system. Further, dosage sensitivity of candidate genes in the region disrupts neurotransmitter signaling and is associated with neuro-behavioral symptoms. Unique DNA repetitive elements in the region are a source of copy number human genetic variation (CNV) and contribute risk for complex diseases like schizophrenia (SCZ). In this mini-review, the topic covering anatomical, genetic and genomics perspectives was reviewed. Repetitive elements analysis of the regions flanking candidate genes was conducted. Additionally, analysis includes network analysis of the PRODH gene to infer interaction proteins and promoter analysis to gain insights into regulatory and chromatin elements. The results indicate a unique repetitive map flanking the genes, which could serve as hotspots for chromosomal rearrangement. The network analysis indicates a hub of 11 genes with a PPI value-(4.59e-06). Unique promoter maps include a CpG island, insulator, gene enhancer and regulatory element (cluster). Chromatin analysis revealed DNASE1 (DNase I hypersensitive) and FAIRE (Formaldehyde Assisted Isolation of Regulatory Elements) regions along with repetitive elements. Cumulatively, the results support the hypothesis of dosage effects of gene/s in the 22q11 region and associated syndrome. The results shed light on the complex phenotype observed at the locus which could be a result either from the overlapping regulation of several genes within this region or through a combinatorial participation in a regulated process such as neurotransmission or signal transduction.